Trinity & beyond [videorecording (DVD)] : the atomic bomb movie - Kuran, Peter; Shatner, William (Distributed by VCE, 2006)
Chronicles the top secret, strange and visually compelling history of the design, production and testing of atomic and hydrogen bombs by the U.S.